2012
DOI: 10.4304/tpls.2.4.734-740
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-linguistic Study of Prepositions in Persian and English: The Effect of Transfer

Abstract: Abstract-The present paper is a contrastive study which attempts to investigate the errors made by Iranian EFL learners due to the cross-linguistic influence between their L1/SL and L2/TL language (i.e. Persian & English respectively). To meet the goals of the study, an error analysis was conducted to examine the status of different types of errors of prepositions made due to the transitional constraints between Persian and English languages. To this end, a translation task was developed by the present researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
(8 reference statements)
1
18
0
Order By: Relevance
“…The findings were consistent with previous findings (Mahmoodzadeh, 2012;Humeid, 2013;Khampang, 1974;Ruangjaroon, 2015).…”
Section: %supporting
confidence: 93%
See 1 more Smart Citation
“…The findings were consistent with previous findings (Mahmoodzadeh, 2012;Humeid, 2013;Khampang, 1974;Ruangjaroon, 2015).…”
Section: %supporting
confidence: 93%
“…English prepositional usage after verbs is highly problematic for second language (L2) learners from a variety of first language (L1) backgrounds (Catalán, 1996;Asma, 2010;Mahmoodzadeh, 2012;Chang, 2012;Humeid, 2013). This problem also occurs among L1 Thai learners of English (Lekawatana et al, 1969;Khampang, 1974;Pongpairoj, 2002;Humphries & Phoocharoensil, 2011).…”
mentioning
confidence: 99%
“…One is between Persian and English by Mahmoodzadeh in 2012. Other studies try to give an account of the prepositions found in a particular language, like a study made by van de Vate in 2006 on Krio.…”
Section: Introductionmentioning
confidence: 99%
“…Results also presented that more errors were made with plural nouns than with mass/non-count nouns. Another study conducted by Mahmoodzadeh (2012) looked into the misusages of prepositions made by 53 adult Iranian EFL intermediate learners.…”
Section: Difficult Elements Of English Grammarmentioning
confidence: 99%